Papua New Guinea the road ahead - Judge, Peter (Australian Government, Department of Foreign Affairs and Trade, Economic Analytical Unit, 2004)
"After years of contraction, macroeconomic conditions in Papua New Guinea are improving thanks to favourable commodity prices and a number of successful policy reforms. But the public sector salaries bill remains too large and development expenditure inadequate. Proposed new natural gas and minerals projects alone will not be sufficient to arrest the erosion of per capita income. The report argues that greater agricultural productivity, increased investment, better management of infrastructure and a stronger private sector will be vital to create income and employment opportunities. Improved roads, social services, utilities, governance and law and order will be needed for Papua New Guinea to sustain growth."--Editor.